Optimization of Shipping Cost of Cement for Selected Construction Projects of Julius Berger - Kenneth Miebaka Oba (International Journal of Engineering and Management Research, 2023)
The Transportation modelling technique was adopted in solving the transportation problem of shipping cement from three supply locations (cement depots) to three demand locations (construction sites) for Julius Berger construction company in Port Harcourt. The research was carried out for standard 900 bag truck load of cement from the selected cement depots. Transportation costs of the cement were analysed and the initial feasible solutions obtained, using the North-West Corner, Least Cost, and Vogel’s approximation methods. The Least Cost method resulted in the most feasible cost. Finally, the optimum shipping cost was attained, using the Stepping stone method, which resulted to an amount of $2,259 or (₦1,716,840 as at April 2023). Alternatively, Microsoft Excel solver was used on a computer in order to draw a comparison of the results. This gave exactly the same results.